2000
DOI: 10.1097/00004714-200010000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Early Termination of Antidepressant Drug Treatment

Abstract: Guidelines for antidepressant drug therapy recommend continuing treatment for several months, even after recovery. Premature termination of medication is viewed as a significant reason for chronicity in depressive disorders. To study the scope and type of this problem, routine treatment cases must be observed in sufficient numbers. In four subsequent drug utilization observation studies, the time course and reasons for early termination (i.e., during the first weeks of fluoxetine treatment for depression) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 41 publications
0
19
0
3
Order By: Relevance
“…We were unable to investigate the reasons for discontinuation, which may have been non-adherence or adverse effects. 24 The database does not record information concerning diagnosis, treatment compliance, or dispensing of prescriptions, which is a limitation of many automated databases.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to investigate the reasons for discontinuation, which may have been non-adherence or adverse effects. 24 The database does not record information concerning diagnosis, treatment compliance, or dispensing of prescriptions, which is a limitation of many automated databases.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted some time ago and in view of the lack of qualitative studies in this field, a further exploration of this aspect particularly related to those participating in programmes in a range of contexts would probably prove valuable. However, even with conventional management such as drug therapy, discontinuation of treatment for depression is a considerable problem; Linden et al (2000) reported rates of termination of antidepressant treatment of between 31-48% in the first 10 weeks while Lawrenson et al (2000) reported that over 50% of patients had ceased treatment in the first 6 weeks.…”
Section: Studymentioning
confidence: 99%
“…Pharmacotherapy compliance in the first 8 weeks of our study can be considered rather fair. Recent reviews [Anderson, 2000;Linden et al, 2000] mention dropout rates of 33-48% in pharmacotherapy conditions within the first 6-8 weeks.…”
Section: Dropout Ratesmentioning
confidence: 99%